Screening of Sugarcane Commercial GMP Varieties Tolerant to Drought Stress Based on Molecular Detection of P5CS Gene - Mahfut Mahfut; Maulidya Ananda; Endah Susiyanti; Rochmah Agustina (Journal of Multidisciplinary Applied Natural Science, 2025)
Sugarcane (Saccharum officinarum L.) requires sufficient a water supply to produce optimal productivity. The selection of the superior varieties of sugarcane that are tolerant to drought can be done by molecular detection of the presence of the pyrroline-5-carboxylate synthetase (P5CS) gene. The research is aimed at molecular detection of P5CS gene in a commercial varieties at PT Gunung Madu Plantations (GMP), Indonesia that are potentially drought resistant. Similar research has never been conducted at PT GMP, as evidenced by the absence of official publications. The varieties used are GMP 3, GMP 5, RGM 06-654, PS 864, RGM 08-1026, PSJT 941, RGM 01-1834, GP11, RGM 07-099, and RGM 02-108. The research phases include DNA isolation, quantitative and qualitative DNA amplification, and PCR product visualization. Molecular data analysis is based on DNA band scoring results in the form of binary data which is then used to calculate the level of polimorphism information content (PIC) on the primary data used. The results of the study showed that nine out of ten varieties had P5CS-specific band sizes of ±167 bp, namely GMP 3, GMP 5, RGM 06-654, PS 864, PSJT 941, RGM 01-1834, GP 11, RGM 07-099, and RGM 02-108. A total of four of the nine varieties showed P5CS gene band thicknesses of RGM06-654, PSJT 941, PS864, and RGM 01-1834 which indicates the selected varieties most resistant to drought. The result of the PIC calculation has a value of > 0.25 which indicates the primary P5CS used is quite informative. The molecular detection was continued on one selected variety is PSJT 941, which showed that the relationship analysis of P5CS gene shows close affinity with the isolates from China and Bogor.